A topical nitric oxide-releasing dexamethasone derivative: effects on intraocular pressure and ocular haemodynamics in a rabbit glaucoma model. Issue 11 (16th August 2006) - Galassi, F; Masini, E; Giambene, B; Fabrizi, F; Uliva, C; Bolla, M; Ongini, E
Abstract : Background: Topical nitric oxide-releasing dexamethasone (NCX1021) may avoid the negative effects of dexamethasone phosphate. Aims: To obtain more information on the role of nitric oxide in glaucoma and to compare a nitric oxide-releasing dexamethasone with dexamethasone phosphate with regard to intraocular pressure (IOP) and ocular haemodynamics in an experimental rabbit model. Methods: Six rabbits were treated with dexamethasone phosphate 0.1% in the right eye and with NCX1021 in the left eye for 5 weeks. The parameters considered were IOP, nitric oxide marker levels in aqueous humour, ocular haemodynamics of ophthalmic artery (by means of colour Doppler imaging), expression of endothelial nitric oxide synthase (eNOS)in ciliary processes and histology of ciliary bodies. Results: Dexamethasone increased IOP levels, NCX1021 did not. Nitrite and cyclic guanosine monophosphate levels in aqueous humour were lowered by dexamethasone and increased by NCX1021. Resistivity index of the ophthalmic artery was increased, eNOS expression was reduced and ciliary bodies showed histological lesions in dexamethasone-treated eyes, not in NCX1021-treated ones. Conclusions: NCX1021 may avoid the IOP increase, impairment of ocular blood flow and the morphological changes in the ciliary bodies possibly induced by corticosteroid treatment.